Letter from the Hon. Secretary of the APL to T. Moran - Anti-Partition League, APL (1939)
Typescript letter dated 10 May 1939, to T Moran from the Hon. Secretary, about a financial guarantee for salaries of organisers in Manchester and Liverpool.